Boris Pilnyak as a Soviet Writer - Baloney, Philip (My University, 1969)
A study of the place of Boris Pilnyak in Soviet Literature faces several practical difficulties; biographical data are scanty, critical material is very scarce, and some of his works are unavailable or difficult to obtain. Until greater latitude is allowed to Soviet scholars and until the author's works are more readily available, non-Soviet scholarship can only render preliminary judgments upon Pilnyak and his works. There is always the possibility that a substantial amount of "desk-drawer literature" by the author will be published at a later date.
The scope of this study is general, the basis of more detailed investigations in the future; Pilnyak is viewecl in the context of the 1920's and 1930's, the period in which he wrote the great majority of his novels and stories. Pilnyak is not only an interesting author, but also worthy of attention as a central figure in the struggle for power between various literary groups or camps.
The first part of this thesis deals with Pilnyak the author -- his concern with the Revolution, his themes, and his characters. The second half of the thesis deals with Pilnyak the literary politician-- his role in the Union of Writers and his difficulties with the Soviet literary and political establishments.
I hope to attain two goals as a result of this study: 1) to shed some light upon Boris Pilnyak as an author and personality; 2) to delineate the fratricidal struggle in the literary arena of the late twenties through the case of Boris Pilnyak.
I have used the transliteration of the name "Pilnyak" which is most common in English; the correct form is "Pil'njak."
All quotes from Pilnyak's works are in Russian, with the exception of those quotation which are llvailahle only in English.
I wish to express my gratitude to Dr. Louis J. Shein, Chairmnn of the De-partment of Russian, McMaster University, and to Dr. C. ,J. G. Turner, for their advice and assistance.
I also wish to thank McMaster University for granting financial assistance in the form of a Graduate Teaching Fellowship.
Keywords: Other Languages, Societies, and Cultures; Other Languages, Societies, and Cultures